Programa de doação de corpos da Universidade Federal do Rio Grande do Norte: análise do perfil do doador e perspectivas - Nicácio, Ivana Lorena de Oliveira (2023)
Human anatomy is an essential academic subject for the formation and qualification of students in health courses. Considered as the first patient of these students, the cadaver plays a fundamental role in the development of the future professional. Due to the increase in the number of medical institutions and the constant concern with the ethical issues related to the use of bodies in the academic field, Body Donation Programs (BDP) have been emerging in a worldwide trend as the main way to acquire bodies for anatomical studies. Although the PDC were created to meet the demand for cadavers needed for teaching human anatomy, this number is still insufficient. Knowing that the donation of bodies is a totally individual, altruistic and voluntary act, understanding the profile of those who donate their own bodies for teaching is important to develop strategies to encourage new donorsto join the PDC. Thus, this study aimed to characterize the PDC of the Federal University of Rio Grande do Norte (UFRN) regarding the profile of the majority donor, as well as to understand the main motivations that have influenced donors over the 40 years of existence of the Program. Data from UFRN's Declarations of Donation and Socioeconomic Forms for Body Donation were used to create a database with categorical and continuous variables about the donors' profile. The main categories analyzed were sex, age, education, religious influence, and the main motivation for body donation. The results, obtained through descriptive statistical analysis, reveal that the PDC of UFRN currently has 249 registered volunteers from the year 1980 to the year 2021. The data analysis shows that 53% of the volunteers are female (n = 131) while only 47% are male (n = 118). Regarding the age range of the donors, although the mean age is 56.6 years, the most representative age range among the volunteers was 58 to 67 years for both genders. The results also show that most of the donors had higher education level (n = 46) and were catholic (n = 33). The main motivations reported by the PDC volunteers at UFRN were related to contributing to the advancement of education and gratitude to science, which suggests altruistic motivational aspects in relation to society as a whole. Taken together, these data lead to the conclusion that the general profile of the majority donor of the UFRN PDC is female, between 58 and 67 years old, with higher education, and catholic. Our findings also signal a discrete relationship between higher levels of education and higher probabilities of individuals becoming body donors. Finally, we observed a considerable increase in the entry of volunteers to the PDC of UFRN in its fourth and last decade of existence (2010 to 2019) and that this increase in donors is due, at least in part, to the increase in advertising campaigns for greater visibility of the Program.